2020
DOI: 10.1515/med-2020-0215
|View full text |Cite
|
Sign up to set email alerts
|

Circulating irisin is linked to bone mineral density in geriatric Chinese men

Abstract: BackgroundWhile there is evidence of a link between irisin and bone metabolism, prior clinical evaluations have been limited to women with postmenopausal osteoporosis. The primary goal of this evaluation is to examine the relationship between irisin and bone mineral density (BMD) in geriatric Chinese men experiencing osteoporosis or osteopenia.MethodsIn this case–control study, 43 geriatric Chinese men were verified as having osteoporosis or osteopenia via dual-energy X-ray light absorption spectrophotometry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…In a case-control study by Zhang et al, geriatric Chinese men with osteoporosis or osteopenia had reduced serum irisin levels compared to age-matched controls without osteoporosis or osteopenia [93]. In addition, multiple linear regression analysis showed that serum irisin levels are an independent factor for bone marrow density (Table 6) [93].…”
Section: Role Of Irisin On Bone Homeostasis: Clinical Evidencementioning
confidence: 99%
“…In a case-control study by Zhang et al, geriatric Chinese men with osteoporosis or osteopenia had reduced serum irisin levels compared to age-matched controls without osteoporosis or osteopenia [93]. In addition, multiple linear regression analysis showed that serum irisin levels are an independent factor for bone marrow density (Table 6) [93].…”
Section: Role Of Irisin On Bone Homeostasis: Clinical Evidencementioning
confidence: 99%
“…FNDC5 and its cleaved circulating form irisin are positively correlated with an active lifestyle ( Tenorio et al, 2017 ). Vigorous-intensity physical activity had a high serum level of irisin ( Morelli et al, 2020 ), which positively related to bone mechanical properties ( Zhang et al, 2020 ). Furthermore, treatment with irisin is found to improve BMD and biomechanical properties in murine models ( Colaianni et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that irisin was linearly correlated with BMD at different bone sites and that there was a systematic association between circulating irisin and bone mass (Colaianni et al, 2017a). Zhang et al (2020) also demonstrated a positive correlation between irisin levels and BMD in older Chinese men in 2020, and these results supported the idea that irisin exerts a protective effect on bone tissue. In 2022, Wang et al investigated the relationship between serum levels of irisin and BMD in patients with newonset type 2 diabetes and observed that decreased serum levels of irisin were negatively associated with BMD.…”
Section: The E Ects Of Irisin On Osteoarthritis Irisin and Bone Miner...mentioning
confidence: 54%